The problem of identification and correction of micro- and macronutrients deficiency after bariatric surgery: A review - Vladimir V. Salukhov; Elena A. Kovalevskaya; Ruslan T. Sardinov (ZAO "Consilium Medicum", 2022)
Surgical treatment of obesity is one of the most effective ways to reduce and maintain body weight for a long time. Depending on the type of operation, patients with different frequency develop malabsorption syndrome. As a result, in individuals who have received this type of medical care, at different times after bariatric surgery, micro and macronutrient deficiencies may be detected. Therefore, the long-term safety of this treatment method is associated with the correction of vitamin and trace element deficiencies both before and after bariatric intervention. This review highlights the most common deficiencies that are found in obese patients, as well as methods for their diagnosis and treatment.